Transfemoral transcatheter aortic valve implantation in patients with end-stage renal disease and kidney transplant recipients. Issue 1 (December 2017) - Al-Rashid, Fadi; Bienholz, Anja; Hildebrandt, Heike; Patsalis, Polycarpos-Christos; Totzeck, Matthias; Kribben, Andreas; Wendt, Daniel; Jakob, Heinz; Lind, Alexander; Jánosi, Rolf; Rassaf, Tienush; Kahlert, Philipp
Abstract Transcatheter aortic valve implantation (TAVI) has evolved to a treatment of choice in high-risk patients and is therefore ideal for patients with advanced chronic kidney disease, as patients with end-stage renal disease and kidney transplant recipients. Especially, outcome of this special patient group is very important. 22 patients with chronic kidney disease stage 5 undergoing intermittent hemodialysis treatment (CKD 5D) and 8 kidney transplant recipients (KT) with severe aortic valve stenosis underwent transfemoral TAVI. TAVI was successfully performed in all patients. Postinterventional acute kidney injury (AKI) occurred in four kidney transplant recipients (KDIGO grade 1: n = 3, grade 3: n = 1) but creatinine/eGFR returned to baseline values in all patients. Short-term (30-day) mortality was 3% (1 patient in CKD 5D group). KT had a higher 2-year mortality than CKD5D patients (31% vs. 53%; p = 0.309), and cause of death was non-cardiac because of sepsis in all cases. The amount of contrast medium during TAVI was not associated with the development of acute kidney injury. TAVI is feasible in patients with CKD5D and in KT. Postinterventional AKI in these patients is often mild and does not impact renal function at day 30, while infection/ sepsis is the leading cause of mid-term mortality.